2016
DOI: 10.3109/02770903.2016.1155219
|View full text |Cite
|
Sign up to set email alerts
|

Adapting and implementing an evidence-based asthma counseling intervention for resource-poor populations

Abstract: Objective To report implementation strategies and outcomes of an evidence-based asthma counseling intervention. The Head-off Environmental Asthma in Louisiana (HEAL) intervention integrated asthma counseling (AC) capacity and addressed challenges facing children with asthma in post-disaster New Orleans. Methods The HEAL intervention enrolled 182 children (4–12 years) with moderate-to-severe persistent asthma. Recruitment occurred from schools in the Greater New Orleans area for one year. Participants receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Among 152 studies in multiracial or multiethnic populations, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , ...…”
Section: Resultsunclassified
“…Among 152 studies in multiracial or multiethnic populations, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , ...…”
Section: Resultsunclassified
“…First, each school should make an effort to develop and implement a systematic and coordinated management protocol for its asthmatic students. As suggested by the National Heart, Lung, and Blood Institute and Thornton et al, the protocol should contain a confidential list of asthmatic children, identified stimuli or triggers causing or worsening asthma and asthma medications the children take, and contact information. The protocol also should include an action plan for monitoring asthma, administering medications, and dealing with proper therapy for an early sign and emergency steps to a severe asthma episode.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…ACs used the CARAT and ERAT output, along with the family's designated priorities, to create a patient-tailored, family-centered intervention. 6,13 ACs conducted at least 4 asthma counseling visits, with at least 1 held in the home. Each family was given an environmental kit similar to the EBI.…”
Section: Intervention Implementationmentioning
confidence: 99%
“…For example, rather than require that ACs have a master's degree in social work, HEAL employed ACs who held master's level education in diverse backgrounds. 13 HEAL also reduced the minimal number of intervention sessions (from ≥5 in person in the EBI to ≥2 in HEAL) 21 to reduce the demand placed on families, who were dealing with multiple conflicting priorities. Pre-post measures in HEAL demonstrated a significant reduction in symptom days (45% reduction; P < .001).…”
Section: Figurementioning
confidence: 99%